The vertical distributions of atmospheric CF2Cl2, CFCl3 and N2O over Syowa Station in 1983 - Hirota, Michio; Makino, Yukio; Muramatsu, Hisafumi (1986)
P(論文) Air samples were collected on an aircraft over Syowa Station up to an altitude of 7.3km on January 24,April 5,October 18 and December 12,1983. Trace gases (CF_2Cl_2,CFCl_3 and N_2O) were measured by a GC-ECD method. These gases were vertically mixed well. Seasonal variation of vertical profiles could not be detected. departmental bulletin paper